2010
DOI: 10.1603/ec09217
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Introducing Exotic Fruit Flies, <I>Ceratitis capitata</I>, <I>Ceratitis cosyra</I>, and <I>Ceratitis rosa</I> (Diptera: Tephritidae), Into Southern China

Abstract: Exotic fruit flies (Ceratitis spp.) are often serious agricultural pests. Here, we used, pathway analysis and Monte Carlo simulations to assess the risk of introduction of Ceratitis capitata (Wiedemann), Ceratitis cosyra (Walker), and Ceratitis rosa Karsch, into southern China with fruit consignments and incoming travelers. Historical data, expert opinions, relevant literature, and archives were used to set appropriate parameters in the pathway analysis. Based on the ongoing quarantine/ inspection strategies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Indeed, Li et al. (2010), who analysed pathways for non‐native fruit flies (i.e. Tephritidae) into southern China, found that the risk of introducing fruit flies with passengers was high when compared to that of introducing fruit flies with fruit imported by sea.…”
Section: Passenger Baggagementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Li et al. (2010), who analysed pathways for non‐native fruit flies (i.e. Tephritidae) into southern China, found that the risk of introducing fruit flies with passengers was high when compared to that of introducing fruit flies with fruit imported by sea.…”
Section: Passenger Baggagementioning
confidence: 99%
“…According to Meurisse et al (2019), Diptera rank second, after Sternorrhyncha hemipterans, in the list of the most frequent insect orders unintentionally transported in passenger baggage. Indeed, Li et al (2010), who analysed pathways for non-native fruit flies (i.e. Tephritidae) into southern China, found that the risk of introducing fruit flies with passengers was high when compared to that of introducing fruit flies with fruit imported by sea.…”
Section: Passenger Baggagementioning
confidence: 99%
“…Li et al . 16 developed a Maxent model for C. capitata focusing on China. Gutierrez and Ponti 12 estimated the invasive potential of C. capitata in California and Italy with the application of a physiologically based demographic system model (CASAS), examining the effect of observed and incrementally increased temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The MaxEnt model of Li et al . 16 was trained on distribution records that included ephemeral populations in northern France. This led to model results suggesting that northern Scotland and parts of Greenland were suitable for C. capitata to establish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation